FORMULATION AND EVALUATION COMBINATION OF ROSE AND JASMINE ESSENTIAL OILS IN AROMATHERAPY PREPARATIONS ON ANXIETY LEVELS OF POSTPARTUM MOTHERS - Venny Diah; Lia Fitria; Siti Nurrosyidah (Poltekkes Kemenkes Medan, 2023)
The birth of a baby should bring joy, but for some women giving birth can be stressful so that it has a physical, social, and psychological impact. One of the psychological aspects that affect postpartum is anxiety. Non-pharmacological therapies that can be used are massage therapy, acupuncture, acupressure, music therapy, yoga, tai chi, hypnotherapy, prayer therapy, and aromatherapy. Aromatherapy that is often used includes sandalwood, jasmine, basil, cloves, lavender, cinnamon. The purpose of this study was to make and evaluate an aromatherapy preparation of a combination of rose and jasmine essential oils on the anxiety level of postpartum mothers. The research conducted was a laboratory experimental. There are 2 research steps, namely (1) making aromatherapy preparations, (2) evaluating aromatherapy preparations which include organoleptic test, homogenity test, clarity test, pH test, and irritation tes. Keywords: anxietylevel of postpartum mothers;rose and jasmine essential ois